Albuminuria Screening in People With Type 2 Diabetes in a Managed Care Organization - Farrah Keong, MPH; Jennifer Gander, PhD; Daniel Wilson, MD; Jeffrey Durthaler, DPh; Belkis Pimentel, MD; Joshua I. Barzilay, MD (Elsevier, 2023)
Introduction: Albuminuria-an increased amount of urine albumin, in milligrams, adjusted for grams of urine creatinine-is an early marker of diabetic kidney disease. Several new classes of medications are now available that effectively lower albuminuria levels with the potential to delay or prevent the progression of diabetic kidney disease. However, screening for albuminuria in the U.S. is low in population-based studies (<10% to ∼50% at most). In this study, we examine whether screening for albuminuria was improved in an integrated model of healthcare delivery following the recommendations of the National Committee for Quality Assurance mandate (an umbrella group for the managed healthcare industry) to screen for albuminuria. Methods: We examined screening for albuminuria over a 2-year period among people with Type 2 diabetes in a U.S. HMO with an electronic medical record, onto which automated laboratory ordering for albuminuria could be added when a patient appeared at the laboratory (for any reason) if albuminuria testing had not been obtained within the previous 365 days. Participants under this plan received diabetes education at no cost and panel managers to guide their diabetes care. Logistic regression using data from 2020 and 2021, separately, evaluated the relationship between patient characteristics and the likelihood of albuminuria screening. Results: There were 20,688 and 22,487 participants with Type 2 diabetes mellitus in 2020 and 2021, respectively, who were analyzed. Approximately 80% were screened for albuminuria in both years. African American participants and those aged >64 years were more likely to have completed albuminuria screening. Screened individuals had lower HbA1c, blood pressure, and low-density lipoprotein cholesterol levels than those who were not screened. Conclusions: In an integrated healthcare model, it is possible to achieve consistently high rates of albuminuria screening in people with Type 2 diabetes, especially in groups at high risk for kidney disease.